An innovative methodology for hybrid vibration control (MR+TMD) of buildings under seismic excitations. Issue 155 (April 2022) - Hosseini Lavassani, Seyed Hossein; Shangapour, Saman; Homami, Peyman; Gharehbaghi, Vahidreza; Noroozinejad Farsangi, Ehsan; Yang, T.Y.
Abstract: In this study, the combination of magnetorheological dampers and tuned mass dampers (MR + TMD) as a hybrid control system is investigated on a 15-story shear building where MR damper is attached to the TMD to generate active control force of TMD. The seismic responses of the structure are reduced by employing MR + TMD on rooftop of the structure. The MR damper's control voltage is generated by combining IT2FLC and FOPID. The FOPID + IT2FLC, TMD, and control voltage parameters are optimized using the observer-teacher-learner-based optimization (OTLBO) algorithm to minimize the maximum displacement of the building rooftop under far-field and near-field earthquake excitations. To conduct additional research, the same method was used to mitigate structural responses for PID, FOPID, IT2FLC, and a combination of fuzzy logic type-1 (FLC) and FOPID (FOPID + FLC). All of these controllers' performances in mitigating seismic responses are compared to those of the uncontrolled system and to each other. The results indicate that FOPID + IT2FLC outperforms PID, FOPID, and FOPID + FLC controllers. Additionally, the building's rooftop displacement was reduced by an average of 35.06% using the FOPID + IT2FLC system for sixteen far-field and near-field earthquake records. Moreover, the hybrid MR + TMD system performs better than other conventional controllers. Highlights: 1 The combined application of the meta-heuristic algorithm and IT2FLC controller along with FOPID controller (FOPID + IT2FLC) to mitigate structural responses. 2 Combined application of MR damper and TMD (MR + TMD) as a hybrid control device. 3 Optimizing FOPID and IT2FLC to generate the control voltage of MR + TMD. 4 Investigating PID, FOPID, FOPID + FLC controllers to compare with the proposed method. 5 Investigating the performance of the suggested method by the aim of energy consumption and 5 novel criteria such as base shear, base moment and etc.